Contribution of Five Functional Loci of Dopamine Metabolism-Related Genes to Parkinson’s Disease and Multiple System Atrophy in a Chinese Population - Chen, Yongping; Ou, Ruwei; Zhang, Lingyu; Gu, Xiaojing; Yuan, Xiaoqin; Wei, Qian-qian; Cao, Bei; Zhao, Bi; Wu, Ying; Shang, Huifang (Frontiers in Neuroscience, 2020)
Background: Impaired dopamine metabolism is associated with Parkinson’s disease (PD). Considering the overlap in the clinical and pathological characteristics between PD and multiple system atrophy (MSA), we investigated the effect of five potential functional polymorphisms in dopamine metabolism-related genes on disease susceptibility, phenotypes, and responses to dopamine in a large sample of PD and MSA patients. Methods: A total of 1,506 PD patients, 496 MSA patients, and 894 healthy controls were included in this study. Five variants (rs6356 in TH, rs921451 in DDC, rs4680 in COMT, rs1799836 in MAOB, and rs1611115 in DBH) were genotyped in all cases using Sequenom iPLEX Assay technology. Results: After adjusting for gender and age at onset, except for DDC rs921451 that was associated with an increased risk of MSA (p=0.001, OR=1.21), no significant differences were found in genotype distribution or minor allele frequencies (MAFs) for the other four variants between PD or MSA patients and healthy controls. In the subgroup analysis, DDC rs921451 was associated with an increased risk for late-onset PD as well as for PD onset in males (p=0.002[OR=1.13] p=0.003[OR=1.15], respectively). In addition, patients harboring the risk allele DDC rs921451 required lower levodopa equivalent daily doses (LEDD) of dopaminergic medication than those without the risk allele (52.00±21.31 mg/day, p=0.015). Conclusion: None of the five candidate functional variants is a major determinant of the risk for PD or MSA. The modified PD phenotypes associated with these variants requires further confirmation.